Temperature Differentially Influences the Capacity of Trichoderma Species to Induce Plant Defense Responses in Tomato Against Insect Pests - Di Lelio, Ilaria; Coppola, Mariangela; Comite, Ernesto; Molisso, Donata; Lorito, Matteo; Woo, Sheridan Lois; Pennacchio, Francesco; Rao, Rosa; Digilio, Maria Cristina (Frontiers in Plant Science, 2021)
Species of the ecological opportunistic, avirulent fungus, Trichoderma are widely used in agriculture for their ability to protect crops from the attack of pathogenic fungi and for plant growth promotion activity. Recently, it has been shown that they may also have complementary properties that enhance plant defense barriers against insects. However, the use of these fungi is somewhat undermined by their variable level of biocontrol activity, which is influenced by environmental conditions. Understanding the source of this variability is essential for its profitable and wide use in plant protection. Here, we focus on the impact of temperature on Trichoderma afroharzianum T22, Trichoderma atroviride P1, and the defense response induced in tomato by insects. The in vitro development of these two strains was differentially influenced by temperature, and the observed pattern was consistent with temperature-dependent levels of resistance induced by them in tomato plants against the aphid, Macrosiphum euphorbiae, and the noctuid moth, Spodoptera littoralis. Tomato plants treated with T. afroharzianum T22 exhibited enhanced resistance toward both insect pests at 25°C, while T. atroviride P1 proved to be more effective at 20°C. The comparison of plant transcriptomic profiles generated by the two Trichoderma species allowed the identification of specific defense genes involved in the observed response, and a selected group was used to assess, by real-time quantitative reverse transcription PCR (qRT-PCR), the differential gene expression in Trichoderma-treated tomato plants subjected to the two temperature regimens that significantly affected fungal biological performance. These results will help pave the way toward a rational selection of the most suitable Trichoderma isolates for field applications, in order to best face the challenges imposed by local environmental conditions and by extreme climatic shifts due to global warming.